Data Governance Practice for Outbound Supply Chain Management (SCM): A Case Study of Malaysian Textile Industry - Mukhrizal, Fizreen Farra; Aziz, Noshakirah AB; Akhir, Emelia Akashah Patah (ExcelingTech, 2019)
The purpose of this paper is to implement a supply chain management (SCM) data governance of outbound logistics for Malaysian textile company. According to this paper, an apparel or textile company was once the top three export earners for manufactured goods of Malaysia. Hence, this research is looking forward to enhancing better performance and business value of Malaysian textile industry which is corresponding with the new application of technology known as â€œIndustry 4.0â€. Without having any standards or guidelines, a company might abortive due to the absence of express semantics and substance of data and information towards integrating and exchanging information among various associates including in the supply chain of the organization. Indeed, changes in policy might also give the impression of instability which impacts the stock prices of a textile company. Hence, this paper focuses on the SCM data governance, whereby the main goal is to identify data governance that exists and must be implemented in compliance with the Malaysian outbound logistic. Throughout this paper, the term data governance is used to refer to the practice of managing all the information to identify and improve the business value of an organization.